Considerations for engaging in patient-oriented research with injured workers - Nagra, Gagan; Hung, Pam; Peters, Meaghan Ray; Guptill, Christine; Ezeugwu, Victor E.; Cooper, Lynn; McKeen, Beverley; Gross, Douglas P. (Frontiers in Health Services, 2025)
BackgroundPatient-oriented research (POR) incorporates patient-identified priorities and lived experiences into research. Despite their central role in return-to-work (RTW) planning, perspectives and priorities of injured workers are under-represented in Occupational Therapy research. Occupational therapists (OTs) play a key role in RTW research and practice, implementing evidence-based plans and patient-centered care, which positions them well to conduct POR.PurposeThe purpose of this paper is to identify considerations for POR approaches for OTs to engage injured workers in RTW research.Key issuesThe engagement of injured workers as research partners is not well described or understood in POR. This paper outlines practical considerations for conducting POR with injured workers, addressing challenges such as power imbalances, communication barriers, fears of unemployment, and varying levels of vulnerability. OTs can facilitate knowledge transfer and act as knowledge brokers within the RTW process, leveraging their client-centered practice to lead research that optimally engages injured workers.ConclusionConducting POR with injured workers can shed light on their interactions with health, insurance, and compensation systems. POR approaches can highlight strengths and limitations of available services and systems and promote improved collaboration and knowledge translation and exchange. OTs can apply POR in research and practice to bridge this gap.